Київські дні Анни Горенко - Степаненко, М. (Слово і Час, 2015)
М. Гумільовим і відомими представниками київської творчої інтелігенції, висвітлено тодішній
мистецький контекст міста, зокрема діяльність журналу “В мире искусств”. The paper considers the early period of Anna Akmatova’s life and work. The author covers Anna
Akmatova’s relationships with M. Gumiliov and other known Kyiv intellectuals and artists. The article
also deals with the artistic context of the life of the city in those times, namely the activity of the
magazine “The world of art”. В статье идет речь о раннем периоде жизни
и творчества Анны Ахматовой. Рассмотрены ее
отношения с Н. Гумилёвым и известными
представителями киевской творческой интеллигенции,
освещен художественный контекст города, в частности
деятельность журнала “В мире искусств”.